The climate crisis as an impetus for learning - Maria Stimm; Jörg Dinkelaker (European Journal for Research on the Education and Learning of Adults)
This contribution examines the kinds of situations in which people begin to learn in the context of the climate crisis. This approach differs from how learning is usually debated in environmental education, which typically focuses on why adults should learn and how this learning can be induced by educational efforts. To understand why and how adults initiate learning, we engage with the debate on concepts of exploring ‘impetuses for learning’ (Lernanlässe), which has been a topic of discussion in the German-speaking context over the past decades. We explore how this concept provides an empirical perspective on the diverse contexts in which adult learning currently occurs and could potentially occur in the future as the climate crisis continues to unfold.